Bioaccumulation of residual omega-3 fatty acids from industrial Schizochytrium microalgal waste using black soldier fly (Hermetia illucens) larvae. (20th September 2020) - El-Dakar, Marco. A.; Ramzy, Remondah R.; Ji, Hong; Plath, Martin
Abstract: Microalgae are considered promising sustainable sources of omega-3 polyunsaturated fatty acids, and those in the genus Schizochytrium are among the most frequently used ingredients in aquaculture feeds. Industrialized Schizochytrium production creates considerable amounts of waste material, the residual fatty acid (FA) content of which could be high. Herein, we described the bioaccumulation of polyunsaturated FAs by black soldier fly ( Hermetia illucens ) larvae feeding on Schizochytrium production waste, which was tested as a hitherto unexploited source of FAs for them. We experimentally reared newly hatched larvae on different substrates consisting of wheat bran and gradually increasing amounts of Schizochytrium waste, comprising from 0 to 50% of the substrate. We assessed their growth rate and final weight at pupation, as well as their content of various FAs, total protein, and total fat. Larvae reared on 50% Schizochytrium waste needed 70% more time (14 days) to develop than controls, while there were no significant differences between the groups fed with 10 and 20% Schizochytrium waste and controls ( P ˃ 0.05) in development time, body weight, and size. However, increasing Schizochytrium concentrations in the feeding media (from 10 to 50%) resulted in significant increases in larval wet weight (mean ± SD: 233.33 ± 7.00 mg), dry matter content (33.32 ± 0.44%), total fat content (38.77 ± 0.95%), and concentrations of polyunsaturated FAs (22.23 ± 0.96%), including omega-3 FAs (11.80 ± 0.84%), among which concentrations of docosahexaenoic acid (DHA) increased by 186.76%. On the other hand, the total protein content and total saturated FA concentration decreased significantly with increasing concentrations of Schizochytrium waste in the feeding media. Hence, rearing black soldier fly larvae on Schizochytrium waste allowed them to accumulate omega-3 FAs (especially DHA), and thus they could be used as a sustainable food additive in aquaculture.